The Influence of Facebook Ads Strategy on Increasing Brand Awareness of Products in Dunia Akrilik - Rizal, Mohammad Sulton Amirur; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to explore and analyze the influence of Facebook Ads strategies on increasing brand awareness and product sales at Dunia Akrilik. Design/Method/Approach : This study uses a quantitative approach with a purposive sampling technique on 40 relevant respondents. Data were collected through an online questionnaire and analyzed using simple linear regression to measure the relationship between Facebook Ads strategy and brand awareness. Research Findings : The results of the analysis show that the Facebook Ads strategy has a significant influence on increasing brand awareness, with a coefficient of determination (R Square) of 0.768. Visual elements and audience segmentation have proven to be the main factors in the success of an advertising campaign. Theoretical contribution/Originality : This study extends the digital marketing literature by focusing on the creative industry, especially art and decoration-based products such as acrylic. Its originality lies in the exploration of visual elements and advertising narratives as determinants of campaign effectiveness. Practitioner/Policy Implications : This study provides recommendations for business actors in designing more effective Facebook Ads strategies, with an emphasis on visual design and audience segmentation to increase product appeal. Research limitations : This study has limitations in the small sample size and does not involve a qualitative approach, so the results may be less representative. Future research is recommended to use a mixed approach and expand the sample size.